Blood and oil in the Orient: A 2023 update - Shimshon Bichler; Jonathan Nitzan (Capital as Power - Toward a New Cosmology of Capitalism, 2023)
The 2023 war between Hamas and Israel elicits many different explanations. As with previous regional hostilities, here too, the pundits and commentators have numerous overlapping processes to draw on - from the struggle between the Zionist and Palestinian national movements, to the deep hostility between the Rabbinate and Islamic churches, to the many conflicts between Israel and Arab/Muslim states, the contentions between the declining superpowers (United States and Russia) and their rising contenders (like China, Iran, Turkey), the rift between western and eastern cultures, and so on. The experts also highlight the growing importance of local militias - from Jewish settler organizations, to ISIS, Hamas, Islamic Jihad, Hezbollah, the Houthi movement, the Wagner Group and Kadyrovites Chechens - groups that operate under different political, religious and criminal guises, with varying financing and support from local, governmental and international sources to proxy and/or challenge different states. Our article does not deal with these specificities. Instead of focusing on the particular and unique, we concentrate on the general and universal. Concretely, we argue that the current war between Hamas and Israel shares an important common denominator with prior clashes in the region - namely, that it constitutes an energy conflict and that it correlates with the differential nature of capital accumulation. We coined these two terms in the late 1980s and have studied their underpinnings and implications for the Middle East and beyond ever since. Our purpose in this paper is to highlight our theoretical arguments, update some of our key empirical evidence and show how both the theory and findings apply to the current Hamas-Israel war.
Keywords: 330; capital as power; corporation; differential accumulation; dominant capital; energy conflicts; Gaza; Hamas; Israel; Middle East; oil; Palestine; prices; Technodollar-Pharmadollar Coalition; profit; war; Weapondollar-Petrodollar Coalition